Implémentation de la leçons interactive Quizizz sur les matières féliciter quelqu’un pour la classe XII à SMA Kesatrian 1 Semarang - Redinda Larasati; Aisyiah Al Adawiyah (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
French learning at SMA Kesatrian 1 Semarang only uses textbooks, and teachers also rarely use learning support media, thus making students feel bored and less interested in participating in learning activities. As many as 100% of class XII Language Students find it difficult to understand the Féliciter Quelqu’un material if learning only using textbooks, 78.6% of students stated that it is very necessary to use learning media, so the use of learning media is considered very necessary to support learning activities. Quizizz Lesson is one of the features of the Quizizz application that can be used as a learning media to help students understand the material taught. It can create a more attractive learning atmosphere to increase student learning motivation. The purpose of this study is to explain the implementation of the Quizizz Lesson in class XII on the Féliciter. Quelqu’un material at SMA Kesatrian 1 Semarang. This study used a qualitative descriptive method. The results of this study show that the application of Quizizz Lesson is very helpful for students. 53.8% of students strongly agreed, and 46.2% agreed that Quizizz’s Lesson helps in understanding the material. Therefore, it can be concluded that Quizizz’s Lesson is very effective to be used as a learning aid to help students understand Féliciter Quelqu’un material during the learning process.